2017
DOI: 10.1097/mog.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into microbiome in colitis and colorectal cancer

Abstract: Purpose of review Microbiota is a major component of the etiology of inflammatory bowel diseases (IBD) and colorectal cancer (CRC). Here, we summarize key advances achieved the past 18 months (ending June 2017) toward a better understanding of the role of microbiota in colitis and CRC development. Recent findings Accumulating evidence shows the essential role of intestinal barrier function (e.g., mucus, IgA, LCN2, LYPD8) in protecting against bacteria-induced inflammation and tumor development. Numerous sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 41 publications
1
53
0
1
Order By: Relevance
“…The proportions of Lactobacillus, one of the common colonic microbiota, are frequently correlated with intestinal diseases like Crohn's disease [24], obesity, type 2 diabetes, and cancer [25], and breast cancer tumor development [26] was found decreased as well. We also found a change in abundance of Alistipes, which may have disease-promoting activities with gut diseases and relatively high incidence in the nipple aspirate fluid from people with breast cancer [27][28][29].…”
Section: Altered Gut Microbiome In the Nude Mice Injected With Wt Mcfmentioning
confidence: 68%
“…The proportions of Lactobacillus, one of the common colonic microbiota, are frequently correlated with intestinal diseases like Crohn's disease [24], obesity, type 2 diabetes, and cancer [25], and breast cancer tumor development [26] was found decreased as well. We also found a change in abundance of Alistipes, which may have disease-promoting activities with gut diseases and relatively high incidence in the nipple aspirate fluid from people with breast cancer [27][28][29].…”
Section: Altered Gut Microbiome In the Nude Mice Injected With Wt Mcfmentioning
confidence: 68%
“…A meta-analysis of 526 fecal shotgun metagenome datasets identi ed a microbial core of seven enriched bacteria in CRC (22). This core set included: ETBF; four oral bacteria of Fusobacterium nucleatum (35,36), P.micra, Prevotella intermedia (37) and Porphyromonas asaccharolytica (38); and two other bacteria, Thermanaerovibrio acidaminovorans (22) and Alistipes negoldii (39). Yachida et al (23) collected stool samples from 616 participants and found these bacteria were apparent in cases of multiple colorectal adenomas and intramucosal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…We also found Lactobacillus decreased in mice with breast cancer cells. In the meantime, we found the abundance change of Alistipes, which may promote digestive diseases, and relatively high incidence in the nipple aspirate fluid from people with breast cancer [23][24][25]. The potential origin of part of breast tissue microbiome may be translocated from the gastrointestinal tract in addition to the skin via the nipple-areolar orifices [44].…”
Section: Discussionmentioning
confidence: 94%
“…The proportions of Lactobacillus, one of the common colonic microbiota, are frequently correlated with intestinal diseases, like Crohn's Disease (CD), obesity, type 2 diabetes and cancer [21], and breast cancer tumor development [22], were found decreased as well. In the meantime, we found the abundance change of Alistipes, which may has disease-promoting activities with gut diseases, and relatively high incidence in the nipple aspirate fluid from people with breast cancer [23][24][25].…”
Section: Altered Gut Microbiome In the Nude Mice Injected With Wt Mcfmentioning
confidence: 90%